Konsep Al-Qalb Dan Al-Aql - Aldila Winda Pramita; Uli Ramadhani; Sulaiman Horta Siregar; Yuda Wira; Candra Nugraha Lubis; Ramadan Lubis (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research aims to analyze the meaning and differences in Islamic theological perspectives, by referring to the text of the Koran. This research uses a library research method which is carried out by reviewing various literature, including previous scientific books and journals that are relevant regarding the concepts of Al-Qalb and Al-Aql. The research results show that a balance between Al-Qalb and Al-Aql is very necessary to achieve harmony in life, both in spiritual, social and intellectual aspects. This concept offers important insight into how both can play a role in forming individuals with noble character and broad insight.